Pharyngomycosis. Diagnostics, prevention and treatment - N. L. Kunelskaya; G. N. Izotova; V. Y. Kunelskaya; G. B. Shadrin; D. I. Krasnikova; O. A. Andreyenkova (Медицинский совет, 2013)
The prevalence of pharyngomycosis was analysed on the basis of research data and own observation of 2,987 patients seeking assistance in the consulting unit of the Centre over the period from 2008 till 2011. The study concluded that the proportion of fungal infections of ENT organs in the total variety of chronic inflammatory disease increased to 29% for fungal infections of the throat in pharyngitis, and to 17.2% in chronic tonsillitis. The pathogens of fungal infections of the throat were defined and analyzed. The study found that the involvement of Candida non albicans strains in the development of chronic inflammation has increased. The proportion of cases of aspergillus infection of the mucous membranes of the pharynx, larynx, and tonsils was identified. Sophisticated diagnosis and treatment schemes were suggested.